Social capital as a mechanism for building a sustainable society in Northern Ireland - Campbell, A; Hughes, J; Hewstone, M; Cairns, E (2010)
In recent years, there has been a general trend in democratic societies to develop and exploit social capital. Reflecting this trend, a recent policy programme for Northern Ireland, A Shared Future, emphasized the importance of relationship building, both within and across communities, and between communities and statutory organizations. The research presented in this paper explores the potential of social capital as a policy concept and the value of the concept for interpreting community dynamics, devising strategies to enhance community relations and development and ultimately building a more sustainable society post-conflict. © Oxford University Press and Community Development Journal. 2008.